CHO‘LPONNING “KECHA VA KUNDUZ” ROMANINING INGLIZ TILIGA TARJIMASIDA SINEKDOXANING IFODALANISHI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article focuses on the expression of the stylistic device of synecdoche in the English translation of Cholpon's novel "Night and Day" by Christopher Fort. It analyzes the similar functions and interrelation of figurative language devices such as metonymy, metaphor, and synecdoche. The article considers synecdoche as a type of metonymy, explaining how it involves expressing a whole through a part or a part through a whole. Uzbek language. The article also presents the definitions of synecdoche given by linguists such as John Bikmen and B. Nerlich, and their views on the need for a deeper study of this stylistic device, distinguishing it from metonymy.
Keywords: Synecdoche, metonymy, cognitive linguistics, cognitivism psycholinguistics, sociolinguist.